Sitagliptin ameliorates microbial dysbiosis and enhances gut barrier integrity in streptozotocin-induced type 2 diabetic rats - Chang, Ying; Zhou, Yuanjiang; Zhou, Fanlin; Liang, Jie; Li, Yu; Tian, Mingyuan (Frontiers in Microbiology, 2025)
BackgroundSitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, has demonstrated efficacy in the management of type 2 diabetes mellitus (T2DM). This study aimed to investigate the effects of sitagliptin on gut microbial composition and gut barrier integrity in a streptozotocin (STZ)-induced rat model of T2DM.MethodsSprague-Dawley rats were randomly divided into four groups (n = 6 per group): a T2DM group induced by high-fat diet (HFD) and STZ injection; a T2DM group treated with oral sitagliptin at 10 mg/kg/day for 12 weeks (T2DM-Sit); a normal diet control group (ND); and a normal diet group treated with sitagliptin (ND-Sit). Fecal samples were collected for 16S rRNA gene sequencing to analyze gut microbial composition and diversity. Intestinal tissues were assessed for tight junction protein expression via immunohistochemistry and western blot.ResultAlpha index metrics, including observed feature number and Shannon index, were significantly decreased in the T2DM group compared to the ND group. Sitagliptin treatment led to a significant restoration of these indices. Principal coordinate analysis based on Bray-Curtis distances revealed distinct clustering between the ND and T2DM groups, with sitagliptin shifting the microbial profile of diabetic rats toward that of healthy controls. Sitagliptin treatment increased the relative abundance of Lactobacillus, Ruminococcus, Streptococcus, Klebsiella, Clostridium_IV, and Romboutsia, while reducing levels of Alloprevotella and Parasutterella, effectively reversing the dysbiotic changes observed in T2DM. Additionally, sitagliptin modulated microbial metabolic pathways, restructured the gut microbial network, and promoted short-chain fatty acid production. Histological and western blot analysis revealed enhanced expression of the tight junction protein ZO-1 and increased numbers of mucin-secreting goblet cells, indicating improved gut barrier integrity.ConclusionSitagliptin effectively ameliorates gut microbial dysbiosis and restores intestinal barrier function in STZ-induced T2DM rats. These findings provide novel insights into the gut-related therapeutic effects of sitagliptin and underscore its potential in restoring gut homeostasis in T2DM.